The Influence of REACT learning strategies on mathematics learning outcomes and learning activities of fifth grade students at SDN Lariangbangi Makassar - Latri Aras; Agusalim Juhari (Universitas Negeri Makassar, 2020)
The results showed that: (1) The average feasibility of learning Mathematics taught using the REACT Learning Strategy was 3.60 out of an ideal score of 4 being in the well-implemented category, (2) The average score of student activity during Mathematics learning being taught by using the REACT Learning Strategy class V SDN Lariangbangi II Makassar is 3.10 out of an ideal score of 4 being in the active category, (3) (a) The average learning outcomes of students taught using the REACT strategy of 86.04 from the Ideal Score 100 and standard deviation 6.05. Descriptively the learning outcomes of students taught with the REACT learning strategy are higher than the KKM value of 78. (b) The average increase in learning outcomes of students taught using the REACT strategy is 0.80 and the standard deviation is 0.09. Descriptively, the increase in learning outcomes of students taught with the REACT strategy is higher than the moderate gain value of 0.3, and (4) (a) There is a significant effect on the REACT Learning Strategy on Mathematics learning outcomes in SDN Class 5 Lariangbangi State Elementary School. (b) Learner activities with the implementation of the REACT strategy which are observed to be overall active in the process of learning activities